The Relationship between Education Level and Mother's Occupational Status with the Nutritional Status of Preschool Children in Kalanganyar District, Lebak, Banten - Maulida Nurkhalisa Malik; Isna Indrawati (Junior Medical Journal, 2023)
Background: Preschoolers are prone to nutritional problems because their health is still unstable while their nutritional needs are increasing. Based on RISKESDAS data for Lebak Regency in 2018, the prevalence of under-fives with malnutrition was 19.6%, normal 71.91%, and more than 8.49%. The role of the mother in nurturing, caring for, and sharpening the child during its growth and development is very important, especially as a regulator of nutritional intake which is related to the mother's education level, mother's occupation, family income level, and mother's level of nutrition knowledge. Method: This study uses a quantitative research type with correlation analysis. The population of this study was all mothers with preschool-age children in Kalanganyar District, Lebak, Banten. 50 samples were taken through quota sampling. Data collection was carried out through interviews using questionnaires, and direct measurements of BB and TB. Data analysis was performed with the chi-square test. Results: 64% of mothers have a high level of education, 92% of mothers do not work, and 72% of preschoolers have normal nutritional status. The statistical test results for the relationship between the mother's education level and the nutritional status of preschoolers obtained p=0.004 (p0.05), while for the relationship between the mother's employment status and the nutritional status of preschoolers it was found p=0.079 (p0.05). Conclusion: There is a relationship between the mother's education level and the nutritional status of preschoolers and there is no relationship between work status and the nutritional status of preschoolers in Kalanganyar District, Lebak, Banten. In the view of Islam, Allah SWT forbade mankind not to leave weak offspring.